Quality of Public Services at Religious State University in The COVID-19 Era - Fatimatuz Zahro Diah Putri Dani; Dian Hafit Syaifullah (Magister Administrasi Publik, 2023)
This research analyzed the service quality of The Religious State University (PTKN) in the era of COVID-19. The research problems for this study can be formulated as: (1) How is the level of satisfaction of service users (students) with the services provided by PTKN in the COVID-19 era? (2) What service elements need to be maintained, improved and repaired the level of satisfaction? This study uses a quantitative method with a survey approach. The sampling technique in this survey is convenience sampling. The service quality measurement instrument refers to Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 14 of 2017, which is scientifically adapted from the five dimensions of ServPerf by Cronin and Taylor. The research result showed that the SQI value of the majority of PTKN surveyed is included in the category of “Very Good” service performance or with the category of service quality “A”. However, online teaching and learning activities (KBM) are new to all PTKN surveyed, so some service providers and service users still have to adapt to this new habit. This is one of the reasons the service application is the lowest element and needs to be repaired.